EVALUATION AND SUPERVISION ON PAI STUDY SUBJECT AT SDIT AL IRSYAD KARAWANG - Akil, Akil; Arifudin, Yadi Fahmi (Edukasi Islami: Jurnal Pendidikan Islam, 2024)
The main problem of this research is due to the low management of educational and learning supervision in Islamic educational institutions in Indonesia. Meanwhile, Al-Irsyad Integrated Islamic Elementary School is one of the leading Islamic schools in Karawang district. This research aims to determine how schools evaluate and supervise Islamic Religious Education learning. The research uses a descriptive qualitative approach using field studies. Data were collected using interviews, observation, and documentation methods. The research results found that the evaluation models are formative and summative. Formative includes daily exams and mid-semester exams. Summative includes final semester exams. Meanwhile, the techniques used are test and non-test techniques. Test techniques include oral and written exams. Meanwhile, non-tests take the form of assignments, performances, and journals. The model used for educational supervision is the clinical model, while the techniques used are individual and group. Individual techniques include classroom visits, observation, personal conversations, and self-assessment. Meanwhile, group techniques are carried out with new teacher orientation activities, teacher meetings, subject-teacher meetings, and workshops. Furthermore, the researcher hopes that the results of this research can become a basis for further research.